2023
DOI: 10.1257/aeri.20210466
|View full text |Cite
|
Sign up to set email alerts
|

Proximity to the Frontier, Markups, and the Response of Innovation to Foreign Competition: Evidence from Matched Production-Innovation Surveys in Chile

Abstract: This paper employs a matched firm production-innovation panel dataset from Chile to explore the response of firm innovation to the increased competition arising from the China shock. The data cover a wider range of innovation inputs and outputs than previously possible and allow generating measures of markups and efficiency (TFPQ) that correspond closely to the concepts of rents and technological leadership envisaged in the Schumpeterian literature. Except for the 10 percent most productive plants that see an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
0
1
0
Order By: Relevance
“…Evidence from Chile suggests that the ''escape-entry'' effect occurs only in about 10% of the most productive firms, while import competition has a depressing effect on innovation in most other firms (Cusolito, Marin, and Maloney 2023). This, in turn, has a negative impact on productivity growth.…”
Section: A Brief Overview Of the Literaturementioning
confidence: 99%
“…Evidence from Chile suggests that the ''escape-entry'' effect occurs only in about 10% of the most productive firms, while import competition has a depressing effect on innovation in most other firms (Cusolito, Marin, and Maloney 2023). This, in turn, has a negative impact on productivity growth.…”
Section: A Brief Overview Of the Literaturementioning
confidence: 99%
“…Bargaining power and its influence on firms' response to foreign competition is a significant aspect; Cusolito et al in [14], conducted a study and revealed that firms with higher markups demonstrate a lesser response in terms of innovation when faced with foreign competition. On the other hand, firms operating closer to the technological frontier tend to respond more actively.…”
Section: Literature Reviewmentioning
confidence: 99%